Effect and Related Mechanism of Platelet-Rich Plasma on the Osteogenic Differentiation of Human Adipose-Derived Stem Cells. (8th August 2022) - Chen, Jufang; Zhang, Yuanyuan; Liu, Mingjin; Zhou, Zongyuan; Li, Qianwen; Huang, Tianjiao; Yue, Yang; Tian, Yulou
Abstract : Objective . Human adipose-derived stem cells (hADSCs) are ideal seed cells for the regeneration of alveolar bone defects. Platelet-rich plasma (PRP), which is rich in growth factors, promotes tissue repair. The purpose of the present study was to investigate whether PRP promotes the osteogenic differentiation of hADSCs and to perform high-throughput sequencing to explore the possible mechanism. Methods . hADSCs were divided into the three following groups: CON group, OM group, and PRP group. Osteogenesis was detected by Alizarin Red staining on day 14. Total RNA was extracted from the OM and PRP groups for high-throughput sequencing. The target genes of the differentially expressed osteogenic-related miRNAs were predicted, and combined miRNA/mRNA analysis was then performed. The mRNA and protein expression levels of hsa-miR-212-5p, type 1 cannabinoid receptor (CNR1), alkaline phosphatase (ALP), Runx2, osteocalcin (OCN), and collagen 1 A1 (COL1A1) in the OM and PRP groups were detected by qRT–PCR and Western blot analyses. The binding between hsa-miR-212-5p and CNR1 was detected by a dual-luciferase reporter assay. Results . Both the OM and PRP groups exhibited enhanced proliferation of hADSCs, and the differences at 48 h and 72 h were statistically significant (P < 0.05 ). The PRP group had significantly more calcium nodules than the CON group (P < 0.05 ). Through high-throughput sequencing analysis, differential miRNA and mRNA expression profiles were obtained. During hADSC osteogenesis, the expression of hsa-miR-212-5p was downregulated, and the expression of CNR1 was upregulated. hsa-miR-212-5p was found to bind directly to the 3′ UTR of CNR1. Conclusions . The present findings indicated that downregulation of hsa-miR-212-5p and upregulation of CNR1 may be involved in the process by which PRP promotes the osteogenic differentiation of hADSCs.